Syariah Branding; Komodifikasi Agama Dalam Bisnis Waralaba Di Era Revolusi Industri 4.0 - Baharun, Hasan; Niswa, Harisatun (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This paper presents the phenomenon that develops in society, related to the existence of religious commodification in business, namely the labeling of